Multiorgan ultrastructural changes in rats induced in synthetic torpor - Salucci, Sara; Hitrec, Timna; Piscitiello, Emiliana; Occhinegro, Alessandra; Alberti, Luca; Taddei, Ludovico; Burattini, Sabrina; Luppi, Marco; Tupone, Domenico; Amici, Roberto; Faenza, Irene; Cerri, Matteo (Frontiers in Physiology, 2024)
Torpor is a state used by several mammals to survive harsh winters and avoid predation, characterized by a drastic reduction in metabolic rate followed by a decrease in body temperature, heart rate, and many physiological variables. During torpor, all organs and systems must adapt to the new low-energy expenditure conditions to preserve physiological homeostasis. These adaptations may be exploited in a translational perspective in several fields. Recently, many features of torpor were shown to be mimicked in non-hibernators by the inhibition of neurons within the brainstem region of the Raphe Pallidus. The physiological resemblance of this artificial state, called synthetic torpor, with natural torpor has so far been described only in physiological terms, but no data have been shown regarding the induced morphological changes. Here, we show the first description of the ultrastructural changes in the liver, kidney, lung, skeletal muscle, and testis induced by a 6-hours inhibition of Raphe Pallidus neurons in a non-hibernating species, the rat.